PENGARUH PEMAHAMAN PERATURAN, SANKSI DAN KESADARAN WAJIB PAJAK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) TERHADAP KEPATUHAN MEMBAYAR PAJAK DI BALIKPAPAN - Hermin Nainggolan; Siti Patimah (Faculty of Economics and Business, Universitas Warmadewa, 2019)
This study aims to determine the effect of understanding the rules, sanctions and awareness of taxpayers of micro, small and medium enterprises (MSMEs) simultaneously on compliance with tax payments in Balikpapan and to find out which of the understanding of taxpayers, sanctions and awareness of taxpayers of micro, small and medium enterprises (MSME) partially which has a dominant influence on Tax Pay Compliance in Balikpapan. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the research on the F test, the value of Fcount> Ftable (26,727> 2,70) at a significant level of 5% (0,000